Physician Residents Shadowing a Certified WOC Nurse to Develop Interprofessional Competencies: A Quality Improvement Project. Issue 1 (January 2022) - Monahan, Laura; Zhao, Meng; Monahan, Michael; Acker, Katelijne; Sandrik, Mary
Abstract : PURPOSE: The aim of this quality improvement (QI) project was to assess a shadowing experience with a certified WOC nurse (CWOCN) on 4 interprofessional collaborative practice domains: interprofessional communication, role awareness and responsibilities, teams and teamwork, and values and ethics for interprofessional practice. PARTICIPANTS AND SETTING: Forty-nine physician residents in Family and Internal Medicine participated in this project set at a health system in Chicago, Illinois. APPROACH: Residents spent 16 hours shadowing a CWOCN and completed the Interprofessional Education Collaborative Competency Self-Assessment Tool (IPESAT) pre- and postshadowing that measured 4 interprofessional education (IPE) domains: interprofessional communication, role awareness and responsibilities, teams and teamwork, and values and ethics for interprofessional practice. Paired t tests were performed to determine differences in IPESAT scores before and after the shadowing experience. OUTCOMES: Residents demonstrated significant improvement in their overall knowledge of IPE ( P = .000) as well as knowledge within each of the 4 domains ( P = .000). After the shadowing experience, the overall ranking improved by 7.5%; the greatest gain (10.8%) occurred in the teamwork domain. IMPLICATIONS FOR PRACTICE: We found that even a comparatively brief shadowing experience with a CWOCN improved knowledge in IPE competencies. The shadowing experience is now permanently part of the Internal Medicine Residency program, and based on these IPE outcomes, other residency programs in our setting, such as the Rehabilitation and Family Medicine program, have increased their requests to shadow with the CWOCN.